2017
DOI: 10.4103/ijo.ijo_740_17
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making and management of uveitic cataract

Abstract: The visual outcome of uveitic cataract surgery depends on the underlying uveitic diagnosis, the presence of vision-limiting pathology and perioperative optimization of disease control. A comprehensive preoperative ophthalmic assessment for the presence of concomitant ocular pathology, with particular emphasis on macula and optic nerve involvement, is essential to determine which patients will benefit from improved vision after cataract surgery. Meticulous examination in conjunction with adjunct investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 103 publications
(167 reference statements)
1
12
1
2
Order By: Relevance
“…According to the Uveitis Guidelines of the Uveitis Society, experts generally believe that except for phacolysis-induced acute uveitis that requires a surgery as soon as possible, other uveitis-induced cataract should receive active anti-inflammatory treatment and suppress intraocular inflammation for one to three months before surgery. Some experts suggested that surgeries should be performed after at least three months of intraocular inflammation suppression [4][5] . Complete obliteration of anterior suspensions or mild aqueous flare are indications for intraocular inflammation suppression.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Uveitis Guidelines of the Uveitis Society, experts generally believe that except for phacolysis-induced acute uveitis that requires a surgery as soon as possible, other uveitis-induced cataract should receive active anti-inflammatory treatment and suppress intraocular inflammation for one to three months before surgery. Some experts suggested that surgeries should be performed after at least three months of intraocular inflammation suppression [4][5] . Complete obliteration of anterior suspensions or mild aqueous flare are indications for intraocular inflammation suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the risk factors for developing sight-threatening cataracts other than DR, all the ophthalmic diseases enrolled in the multivariate analysis were correlated with the occurrence of sight-threatening cataracts. Glaucoma, uveitis and TPPV are known risk factors for cataract formation [ 4 , 5 , 9 ], and advanced age and inflammatory reactions in both DED and AMD may result in increased cataract development [ 38 , 39 ]. Cardiovascular diseases and inflammatory diseases are the two groups of systemic diseases associated with a higher cataract occurrence, but the exact pathophysiology needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted in Asia and Oceania, the prevalence of cataract-induced blindness and moderate-to-severe visual impairment in the general population was more than 35% [ 3 ]. The associated ocular morbidities of cataracts include glaucoma and uveitis, and they can both lead to impaired vision [ 4 , 5 ]. Surgical management is always indicated for sight-threatening cataracts, although some complications may occur after surgery, such as postoperative endophthalmitis and cystoid macular oedema [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from Varner,[ 3 ] Chan et al . [ 4 ] and Rosenberg et al . [ 5 ] literature describing the occurrence of pupillary inflammatory membrane as a separate entity, mimicking cataract and surgical handling of such a non-resolving thick fibrotic uveitic membrane and technique of its removal with an underlying clear lens in pediatric uveitis was found lacking.…”
Section: Discussionmentioning
confidence: 99%